PICKLE FROM BLOOD CLAM (ANADARA GRAMOSA) MEAT - GUPTA, S S; BASU, SUBRATA (Fishery Technology, 2017)
A pickle was prepared from blood clam ( Anadara granosa) meat. The pickle was subjected to biochemical, bacteriological and organoleptic tests at different stages of storage. The pickle has a shelf-life of more than 5-i months at ambient temperature.